2006
DOI: 10.1158/1535-7163.mct-05-0384
|View full text |Cite
|
Sign up to set email alerts
|

A Ferrous-triapine complex mediates formation of reactive oxygen species that inactivate human ribonucleotide reductase

Abstract: Ribonucleotide reductase plays a central role in cell proliferation by supplying deoxyribonucleotide precursors for DNA synthesis and repair. The holoenzyme is a protein tetramer that features two large (hRRM1) and two small (hRRM2 or p53R2) subunits. The small subunit contains a di-iron cluster/tyrosyl radical cofactor that is essential for enzyme activity. Triapine (3-aminopyridine-2-carboxaldehyde thiosemicarbazone, 3-AP) is a new, potent ribonucleotide reductase inhibitor currently in phase II clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
149
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(167 citation statements)
references
References 25 publications
16
149
0
2
Order By: Relevance
“…Methemoglobinemia is a recognized complication of 3-AP administration, and has been linked to the generation of reactive oxygen species [16,17]. The development of clinically significant met-Hg with 3-AP use was initially reported in patients with G6PD deficiency [13].…”
Section: Discussionmentioning
confidence: 99%
“…Methemoglobinemia is a recognized complication of 3-AP administration, and has been linked to the generation of reactive oxygen species [16,17]. The development of clinically significant met-Hg with 3-AP use was initially reported in patients with G6PD deficiency [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the Triapine-Fe(II) complex was significantly more active at inhibiting ribonucleotide reductase than free Triapine (20). Triapine did not remove Fe from the active site of R2 or p53R2.…”
Section: New-generation Lipophilic Fe Chelatorsmentioning
confidence: 97%
“…Triapine did not remove Fe from the active site of R2 or p53R2. Instead, this chelator formed a complex with Fe(III), which was reduced to Fe(II) that generated reactive oxygen species and quenched the ribonucleotide reductase tyrosyl radical (20). This inactivated the enzyme and prevented DNA repair and synthesis (20).…”
Section: New-generation Lipophilic Fe Chelatorsmentioning
confidence: 99%
“…A képzõdõ vas(II)-TSK komplex közvetlenül vagy még inkább az oxigénnel való reakciója során képzõdõ reaktív oxigén származékok (ROS) által képes a katalitikus centrumban lévõ Tyr gyököt kioltani, ami az enzim inaktiválásához vezet. 11 Ennek következtében a TSK-k vas(II/III)ionokkal képzett komplexeinek oldatbeli stabilitása és redoxi tulajdonsága egyértelmûen befolyásol(hat)ja a TSK-k biológiai hatását.…”
Section: áBra Tioszemikarbazon (Tsk) Alapváz (A) Klinikai Vizsgálatunclassified